EFEKTIVITAS MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA SUB MATERI REAKSI PENGENDAPAN DI KELAS XI IPA SMA MUHAMMADIYAH 1 PONTIANAK - Gustiah Gustiah; Dedeh Kurniasih; Fitriani Fitriani (Jurnal Ilmiah Ar-Razi, 2018)
Student learning outcomes were influenced by learning model which applied by teacher. One of the learning model required active student involvement in the learning process was the guided inquiry approach. The guided inquiry learning model emphasized on the discovery and mastery of the concept through the experimental process. This research aimed to identify between the differences of student’s learning outcomes by using guided inquiry learning model and using direct learning model on the sub-material of deposition reaction and the influence of guided inquiry learning model on students’ learning outcomes. This research used quasi experimental design and this purposive sampling technique to determine the sample. The sample of research was the students of grade XI IPA SMA Muhammadiyah 1 Pontianak. Data collection used a test and observation method. Data analysis used SPSS 17.0 for Windows. Based on the result, there were differences between learning outcomes using guided inquiry learning model and direct learning model. This research used Effect Size (ES) with ES = 2,44 as high category with 49,27%, mean guided inquiry learning model gave high effectiveness to students’ learning outcomes. Based on the research results, the guided inquiry learning model was effectively applied in SMA Muhammadiyah 1 Pontianak.Keywords: Learning outcomes, Guided inquiry, Deposition reaction